Comparison of Quality of Life, Satisfaction with Life, and Satisfaction with Orthopedic Shoes among Veterans with Lower Extremities Length Discrepancy Receiving Services and Not-receiving Services after Two Years of Follow-up - Zh. Heidari; A. Karimi; A. Yavari; M. Masoumi; Z. Vali; E. Faraji (Afarand Scholarly Publishing Institute, 2018)
Aims: That the services should be presented suitably tailored to the status of individuals is of high importance in health needs assessment. The aim of this study was to compare the quality of life, satisfaction with life, and satisfaction with orthopedic shoes among veterans with lower extremities length discrepancy receiving services and not-receiving services after two years of follow-up. Materials and Methods: This descriptive study was conducted among veterans with lower extremities difference in West Azarbaijan Province, Iran in 2014 and followed-up in 2016. A total of 76 veterans were selected by purposeful sampling, 48 of whom received prescriptive services (group 1) and 28 of whom received no services (group 2). The research tools were a Quality of Life Questionnaire, Satisfaction with Life Scale, and a researcher-made satisfaction with orthopedic shoes questionnaire. The data were analyzed by SPSS 20, using Chi-square, independent t-test, dependent t-test, Wilcoxon, and Mann-Whitney U test. Findings: Of veterans, 76.6% who had received orthopedic shoes were satisfied. In group 1, the difference of the evaluation of 2014 and 2016 was significant in mental health and physical health, but it was not significant in the overall score of quality of life, while in group 2, the overall quality of life score decreased significantly. The two groups did not have a significant difference in life satisfaction. Conclusions: Most veterans who use orthopedic shoes are highly satisfied. Veterans who received services after a two year follow-up have higher levels of physical health, mental health, and quality of life compared with the veterans who did not use the services. The two groups do not differ in their levels of satisfaction with life.